Social categories and agency within a Conservation Agriculture framework in Laikipia, Kenya. Issue 6 (1st November 2020) - Sousa, Joana; Rodrigues, Paulo; Basch, Gottlieb
ABSTRACT: Since the 1990s Conservation Agriculture (CA) has been presented to smallholders in Laikipia (Kenya) as a strategy to improve both soil fertility and productivity. In this paper, we provide a historical and social analysis of categories used to define soil management practices and farmers by agricultural programmes in colonial and post-colonial Kenya. For this purpose, we have conducted archive research, recorded the social memory of agricultural policies and farming techniques, and examined contemporary conceptual frameworks and institutional networks around CA in Ethi and Umande in Laikipia County, Central Kenya. We identified evidence of historical continuity in the strategies and methods of agricultural promotional practices. CA networks have broadly advertised the advantages of CA as a means to revert soil degradation and improve livelihoods. However, farmer categorizations based on engagement with CA, promotional strategies, and unclear operational definitions have all prevented CA from being understood by farmers as a technological farming proposal. Instead its adoption is linked with social status and occasional free access to agricultural inputs. Additionally, information about the potential risks and limitations of CA should be explicitly made available to farmers in Laikipia in order to promote transparency and informed decision-making.